Method for preparing LLZO nano-powder through keratin-assisted sol-gel method and application of LLZO nano-powder

The keratin-assisted sol-gel method is used to prepare LLZO nanopowders, which solves the problems of complex process and environmental unfriendliness in the existing technology and realizes the preparation of high-performance LLZO nanopowders for application in all-solid-state batteries and lithium metal batteries.

CN120757143APending Publication Date: 2025-10-10ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510791767.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The existing LLZO nanopowder preparation process is complex, energy-intensive, has poor particle uniformity, and is environmentally unfriendly, making it difficult to prepare high-performance cubic phase LLZO nanopowder.

Method used

The keratin-assisted sol-gel method was adopted, and keratin extracted from waste wool was used as a natural complexing agent and template. Through adjusting the pH value, stirring, drying and calcination steps, cubic phase LLZO nanopowders with high crystallinity and uniform particle size were prepared.

Benefits of technology

The preparation process has been simplified, and LLZO nanopowders with small particle size (30-100 nm), high crystallinity and high purity have been achieved, which has improved the ionic conductivity and environmental friendliness of the material and is suitable for all-solid-state batteries and lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120757143A_ABST
    Figure CN120757143A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing LLZO nano-powder through a keratin-assisted sol-gel method and application of the LLZO nano-powder. The method comprises the following steps: mixing keratin from waste wool and other sources with precursors such as a lithium source, a lanthanum source, a zirconium source, an aluminum source, a niobium source and the like in an aqueous solution to form a uniform and stable precursor solution; heating and stirring the solution to form sol, and performing high-temperature drying treatment to form gel; and finally calcining the gel precursor at high temperature to obtain a target product. Keratin is used as a natural macromolecular complexing agent and an organic template, uniform dispersion of metal ions in a precursor is effectively promoted, the preparation process is simplified, and the cubic phase LLZO nano powder with the particle size of 30-100 nm, high purity and high crystallinity is successfully prepared through an Nb / Al co-doping strategy. The method is green and environment-friendly, high-value utilization of waste resources is realized, and the obtained powder has excellent ionic conductivity and electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolyte materials, and in particular to a method for preparing LLZO nanopowder by a keratin-assisted sol-gel method and application thereof. Background Art

[0002] With the rapid development of mobile electronic devices, electric vehicles and large-scale energy storage systems, lithium-ion batteries have become the core energy storage technology due to their high energy density and good cycle stability. In order to further improve the safety and energy density of lithium batteries, all-solid-state lithium metal batteries (ASSLBs) have received widespread attention. Among them, cubic phase Li7La3Zr2O 12 (LLZO) has become one of the most promising solid electrolyte materials due to its excellent ionic conductivity and chemical stability.

[0003] However, LLZO exists in multiple crystalline phases, among which the cubic phase has high ionic conductivity, while the tetragonal phase, which is stable at room temperature and has ionic conductivity several orders of magnitude lower, is the most stable. To stabilize the highly conductive cubic phase, element doping and high-temperature sintering (usually above 1000°C) are usually required.

[0004] At present, the mainstream methods for preparing LLZO powder include high-temperature solid-phase method and sol-gel method. The high-temperature solid-phase method is simple, but it usually requires a high calcination temperature and long-term heat preservation, which consumes a lot of energy. In addition, the product particles are uneven in size and easy to agglomerate, making it difficult to obtain nano-scale uniform powder. The sol-gel method can achieve uniform mixing of precursors at the atomic or molecular level, thereby reducing the synthesis temperature, shortening the reaction time, and better controlling the morphology and particle size of the product. However, the traditional sol-gel method often uses expensive alcohol salts as precursors, or the process steps are cumbersome.

[0005] Furthermore, the field of materials synthesis is gradually moving towards green environmental protection and resource recycling. Waste wool, a rich natural protein resource, contains a large amount of keratin, which has excellent biocompatibility and multifunctional coordination capabilities. Using keratin extracted from waste wool as a natural chelating agent can effectively promote the uniform dispersion of metal ions, refine nanoparticle size, and improve crystallization quality. Furthermore, the carbonized keratin product helps improve particle morphology and conductivity, achieving efficient resource utilization and environmentally friendly preparation.

[0006] However, the existing technology still lacks the utilization of waste wool resources and the combination of the advantages of the sol-gel method to prepare cubic LLZO nanopowders with high phase purity, uniform and controllable particle size and excellent performance in a more environmentally friendly and simpler process. Summary of the Invention

[0007] The present application aims to solve the problems of complex preparation process, high energy consumption, poor particle uniformity and environmental unfriendliness of LLZO nanopowder in the prior art, and provides a method for preparing high-performance cubic phase LLZO nanopowder by a keratin-assisted sol-gel method, which is simple, green, environmentally friendly and low in cost.

[0008] The technical scheme adopted by the present application to solve the technical problems is:

[0009] A method for preparing LLZO nanopowder by a keratin-assisted sol-gel method, comprising the following steps: S1: preparing a precursor solution: adding keratin, lithium source, lanthanum source, zirconium source, aluminum source and niobium source into water and fully dissolving them, and adjusting the pH to 7-9 to obtain a uniform precursor solution; S2: forming a sol: stirring the precursor solution at 80-90 DEG C for 30-60 min to form a stable sol; S3: forming a gel: drying the sol at 220-250 DEG C to obtain a gel precursor; S4: calcining: heating the gel precursor to 930 DEG C-950 DEG C at a heating rate of 5-10 DEG C / min, and keeping the temperature for 2-3 hours, and then crushing after natural cooling to obtain the LLZO nanopowder.

[0010] In S1, the initial pH of the solution is adjusted to the neutral to slightly alkaline range (pH is 7-9), which is beneficial to the formation of stable complex coordination structure of metal ions and carboxyl and amino groups in keratin molecules, preventing early precipitation. In S2, keratin not only acts as a natural complexing agent, uniformly disperses metal ions and prevents agglomeration, but also provides an organic structure template for subsequent gel and calcination processes. In S3, the uniform sol is dried at 220-250 DEG C to fully remove water and organic components, forming a brown gel with uniform structure and porosity, wherein the keratin part is carbonized, which is helpful for crystal nucleus formation and particle dispersion. During S4 calcination, the complex is completely decomposed, and the metal salt undergoes thermal decomposition and mutual reaction, finally forming high-crystallinity, pure cubic phase Li7La3Zr2O 12 (LLZO) nanoparticles. The microporous structure induced by decomposition of the keratin carbon source effectively controls the nanoparticle size and dispersity, promotes grain refinement, and improves the ion conductivity of the material. After calcination and cooling to room temperature, a uniform and fine LLZO nanopowder is obtained by using a mortar to grind and crush.

[0011] The present application uses keratin from waste wool and other sources as a natural complexing agent and a template agent, effectively promoting the uniform dispersion of metal ions in the sol-gel process and inhibiting particle agglomeration, thereby preparing cubic phase LLZO nanopowder with a particle size of 30-100 nm, high crystallinity and high purity. The method is simple, realizes the utilization of waste resources, and the obtained powder has excellent ion conductivity.

[0012] As a preferred, the keratin in S1 is obtained by treating waste wool in alkaline reducing solution, followed by chain breaking, precipitation, centrifugation, washing and drying. Specifically, the extraction of the keratin is carried out using 0.5-1 mol / L aqueous NaOH or KOH, assisted by 0.1 mol / L Na2S, 0.05 mol / L Na2S2O3 or 0.05 mol / L mercaptoethanol as a reducing agent. The precipitation process in the extraction of the keratin is by slowly adding 1 mol / L hydrochloric acid solution to adjust the pH of the system to 4-5, thereby promoting the analysis of the keratin.

[0013] For keratin extraction and purification, preferably using an alkaline solution method, first soak and scrub approximately 50g of waste wool in room temperature deionized water for 3-5 times, 10 minutes each time, to remove surface dust, grease, residual dye, and mechanical impurities. The cleaned wool sample is then dried in a 60°C vacuum oven for 12 hours, until the mass remains constant. After drying, the wool is cut into 1-5mm segments with scissors or gently crushed in a grinder to significantly increase the fiber surface area, facilitating the penetration and decomposition of the alkaline solution. Weigh 10g of shredded wool and place it in a 500mL three-necked flask. Add 200mL of a 0.5-1mol / L NaOH or KOH solution (pre-prepared with deionized water, pH ≈ 13-14). Add approximately 0.1mol / L sodium sulfide (Na2S), 0.05mol / L sodium thiosulfate (Na2S2O3), or 0.05mol / L mercaptoethanol as a reducing agent to assist in cleaving the disulfide bonds (-SS-) in the keratin. Stir the reaction in a 60-100°C water bath or oil bath for 2-4 hours at a constant stirring speed of 300-500rpm to ensure uniform heating and prevent fiber entanglement. During this process, the alkaline conditions partially cleave the peptide bonds in the keratin backbone and dissolve the keratin in the wool matrix, producing a transparent brown-yellow or light yellow solution. After the reaction is complete, filter the solution while hot through a Buchner funnel and alkali-resistant filter paper to separate solid impurities such as undissolved fibers, lipids, and ash. The resulting filtrate, approximately 150-180 mL, is slowly adjusted to pH 4-5 (the isoelectric point of keratin) by adding 1 mol / L hydrochloric acid (HCl) dropwise. A large amount of pale yellow or off-white flocculent precipitate will be visible in the system. The precipitate should be allowed to stand for 30 minutes with stirring to completely precipitate the keratin. The precipitate is then collected by centrifugation at 5000 rpm for 10 minutes, the supernatant discarded, and resuspended in deionized water and washed 3-5 times until the conductivity of the wash solution approaches 0.5-1 μS / cm (deionized water conductivity) to remove residual alkali, salts, and small molecular byproducts. Finally, the wet keratin precipitate is frozen (-20°C for 12 hours) and then dried in a freeze dryer (-50°C for 48 hours) or a vacuum oven (40°C for 12 hours) to obtain a light yellow, loose powder, representing the purified keratin. Throughout the entire process, the alkali concentration, temperature, and reaction time must be precisely controlled. Excessively high alkali concentrations (>1 mol / L) or prolonged reaction times (>4 hours) can lead to severe degradation of keratin molecules, affecting the subsequent mechanical properties and functionality of the material. Low alkali concentrations or insufficient temperatures can lead to insufficient dissolution, affecting recovery. If necessary, dialysis (MWCO 3500 Da) or ultrafiltration can be used to further remove small molecule impurities and obtain high-purity keratin raw materials.

[0014] Preferably, in the precursor solution of S1, the molar ratio of each metal element is: Li is 6.5-7.5; La is 2.8-3.2; Zr is 1.8-2.2; Al is 0.1-0.5; Nb is 0.05-0.3; based on 100 mL of water, the amount of keratin used is 20g-60g. More preferably, in the precursor solution of S1, the molar ratio of each metal element is Li:La:Zr:Al:Nb=7:3:2:0.25:0.15. The co-doping of Al and Nb here is intended to more effectively stabilize the cubic phase structure of LLZO through a synergistic effect, thereby improving the ionic conductivity of the final product.

[0015] Preferably, in the precursor solution in step S1, the amount of keratin used is 20g-30g, preferably 25g, based on 100mL of water. Keratin serves not only as a gel skeleton, but more importantly as a natural macromolecular complexing agent. The functional groups on its molecular chain can react with Li in the solution. + , La 3+ , Zr 4+ , Al 3+ , Nb 5+ The metal ions are evenly "anchored" on the keratin molecular chain through coordination and complexation, effectively preventing the hydrolysis and precipitation of metal salts (especially easily hydrolyzed salts such as niobium pentachloride) in aqueous solution, and ensuring the uniformity and stability of the precursor solution.

[0016] Preferably, in S1, the lithium source is lithium hydroxide, the lanthanum source is lanthanum nitrate, the zirconium source is zirconyl nitrate, the aluminum source is aluminum nitrate, and the niobium source is niobium pentachloride.

[0017] Preferably, magnetic stirring at 600 rpm is used during the formation of the S2 sol for 30-60 min to improve uniformity and reaction activity.

[0018] Preferably, the sol drying method in S3 is selected from electric heating blast drying or vacuum drying to ensure that the organic matter is fully volatilized and the porous structure is maintained.

[0019] Preferably, the calcination process in S4 is carried out in an air atmosphere, with a heating rate of 5-10°C / min, a maximum temperature of 950°C, and a constant temperature of 2 hours.

[0020] Preferably, the drying temperature in step S3 is 250°C, and the drying time is 2-3 hours. This temperature not only effectively removes moisture but also promotes initial crosslinking and polymerization of the keratin-metal ion complex, forming a structurally stable three-dimensional network gel. Keratin acts as an organic template in this process. The microporous structure formed after carbonization provides uniform space for the formation and growth of crystal nuclei during the subsequent calcination process, facilitating the formation of fine and well-dispersed nanoparticles.

[0021] An LLZO nanopowder prepared by any of the above methods. The obtained LLZO nanopowder has a particle size range of 30-100 nm, a stable cubic phase crystal structure, and an impurity content of less than 2%.

[0022] The present invention discloses an application of the LLZO nanopowder in the preparation of a solid electrolyte membrane. Specifically, the LLZO nanopowder is introduced as an inorganic filler into a polymer matrix to enhance its ionic conductivity and mechanical strength, thereby improving the overall performance of the solid electrolyte membrane.

[0023] The present invention discloses an application of the LLZO nanopowder in stabilizing the interface of a lithium metal anode. Specifically, the LLZO nanopowder is applied as an interface material to the surface of a lithium anode, effectively improving interface stability, inhibiting lithium dendrite growth, and extending cycle life.

[0024] The present invention discloses an application of the LLZO nanopowder in the preparation of cathode materials. The LLZO nanopowder is used to match high-nickel or lithium-rich cathode materials to improve their high-voltage cycling stability and electrode-electrolyte interface compatibility.

[0025] The beneficial effects of the present invention are:

[0026] 1. The present invention innovatively uses keratin extracted from waste wool as the raw material for preparing LLZO nanopowder, turning a common biomass waste into a high-value-added material, which is in line with the development concepts of green chemistry and circular economy.

[0027] 2. The present invention utilizes keratin as a natural macromolecular complexing agent and gel template to uniformly disperse a variety of metal ions in the sol-gel system, effectively avoiding the agglomeration and uneven precipitation of metal ions. The one-step drying and gelation process simplifies the process, ultimately obtaining nanopowders with a small particle size (30-100 nm) and good dispersibility.

[0028] 3. The present invention successfully prepares high-purity cubic LLZO at a relatively low calcination temperature (950°C) through the synergistic co-doping of Nb and Al and the uniform distribution of elements achieved by the sol-gel method. The room temperature ionic conductivity of the LLZO can reach 4.19 × 10 -4 S cm -1, showing excellent cycle stability and high capacity retention in all-solid-state batteries. The prepared LLZO nanopowder has the excellent characteristics of effectively stabilizing the cubic phase and excellent electrochemical performance.

[0029] 4. This invention innovatively utilizes a one-step sol-gel method to prepare LLZO nanopowders. Compared to traditional solid-phase reaction or multi-step sol-gel methods, this significantly simplifies the preparation process. By precisely controlling the formulation, pH, and reaction conditions, the precursor solution preparation, sol formation, gel drying, and final calcination are seamlessly integrated, eliminating the need for intermediate product separation and multiple handling processes, thereby improving production efficiency. This one-step method, combined with the complexing effect of keratin, enables uniform mixing of the metal components at the molecular level, facilitating the formation of highly crystalline, pure-phase LLZO nanopowders. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a flow chart of the preparation of LLZO in Example 1 of the present invention.

[0031] Figure 2 This is the X-ray diffraction (XRD) pattern of the LLZO nanopowder prepared in Example 1 of the present invention.

[0032] Figure 3 is a scanning electron microscope (SEM) image of the LLZO nanopowder prepared in Example 1 of the present invention;

[0033] Figure 4 2 is the AC impedance spectra (Nyquist plots) of the LLZO ceramic pellets prepared in Examples 1 and 7 of the present invention at 25° C.

[0034] Figure 5 is a comparison chart of ionic conductivity of embodiments of the present invention;

[0035] Figure 6 : is the charge-discharge cycle performance curve of the solid-state battery assembled with a PEO-based all-solid electrolyte based on LLZO as a filler in Example 8 of the present invention;

[0036] Figure 7 is a long cycle diagram of the lithium metal anode modified by LLZO in Example 9;

[0037] Figure 8 is a long cycle diagram of the lithium metal anode without LLZO modification in Example 9;

[0038] Figure 9 1 is a comparison diagram of stress-strain curves in Example 10;

[0039] Figure 10 is a scanning electron microscope (SEM) image of the LLZO nanopowder prepared in Comparative Example 1 of the present invention;

[0040] Figure 11 This is the X-ray diffraction (XRD) pattern of the LLZO nanopowder prepared in Comparative Example 1 of the present invention:

[0041] Figure 12 is a scanning electron microscope (SEM) image of the LLZO nanopowder prepared in Comparative Example 2 of the present invention;

[0042] Figure 13 is the X-ray diffraction (XRD) pattern of the LLZO nanopowder prepared in Comparative Example 2 of the present invention; DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described in detail below through specific examples. It should be understood that the implementation of the present invention is not limited to the following examples, and any form of modification and / or change made to the present invention will fall within the scope of protection of the present invention.

[0044] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used are commercially available or commonly used in the art. The methods in the following examples are all conventional methods in the art unless otherwise specified.

[0045] Unless otherwise specified, the reagents used in the following examples can be purchased from conventional biochemical reagent stores.

[0046] Reagents such as lithium hydroxide (LiOH·H2O), lanthanum nitrate (La(NO3)3·6H2O), zirconium nitrate (Zr(NO3)4·5H2O), aluminum nitrate (Al(NO3)3·9H2O) and niobium pentachloride (NbCl5) Na2S2O3 were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0047] Example 1: Preparation of cubic Li7La3Zr2O by one-step sol-gel method assisted by waste wool keratin 12 (LLZO) nanopowder

[0048] This embodiment provides a one-step sol-gel method using waste wool keratin to prepare high crystallinity and high dispersion cubic phase Li7La3Zr2O 12 (LLZO) nanopowder method, the specific steps are:

[0049] 1. Pretreatment of waste wool:

[0050] Weigh 50g of waste wool (source: textile mill scraps) and repeatedly soak and scrub it three times (10 minutes each time) in room temperature deionized water to thoroughly remove impurities. Dry the washed wool sample in a vacuum oven at 60°C for 12 hours.

[0051] 2. Keratin extraction and purification:

[0052] 50 g of shredded wool was weighed and placed in a 500 mL three-necked flask. 200 mL of 0.8 mol / L aqueous NaOH (pH approximately 13.5) and 0.05 mol / L Na₂S₂O₃ as a reducing agent were added. The reaction was stirred in an 80°C water bath for 3 hours at 400 rpm. After the reaction, the mixture was filtered through a Buchner funnel to separate solid impurities, including undissolved fibers. The resulting filtrate, approximately 160 mL, was adjusted dropwise to a pH of 4.5 with 1 mol / L hydrochloric acid (HCl). The mixture was allowed to stand for 30 minutes to completely precipitate the keratin. The precipitate was then collected by centrifugation and washed four times with deionized water to remove any residual salt ions. Finally, the wet keratin precipitate was freeze-dried to obtain purified keratin powder.

[0053] 3. Preparation of precursor solution:

[0054] The following analytically pure raw materials were accurately weighed in a molar ratio of Li:La:Zr:Al:Nb = 7:3:2:0.25:0.15: 25g of keratin powder, 3.0g of lithium hydroxide (LiOH·H2O), 9.7g of lanthanum nitrate (La(NO3)3·6H2O), 6.2g of zirconium nitrate (Zr(NO3)4·5H2O), 0.2g of aluminum nitrate (Al(NO3)3·9H2O), and 0.1g of niobium pentachloride (NbCl5). All weighed raw materials were added to 150mL of deionized water and stirred under magnetic stirring until completely dissolved. The pH of the solution was precisely adjusted to 7.5±0.1 by dropwise addition of dilute nitric acid (0.1 mol / L), resulting in a homogeneous, transparent precursor solution.

[0055] 4. Sol Formation: The precursor solution was placed in an 85°C water bath and magnetically stirred at 600 rpm for 45 minutes. During this process, the solution gradually became viscous and eventually formed a stable, transparent sol.

[0056] 5. Gel drying: The obtained sol is carefully transferred to a high-temperature resistant ceramic dish and placed in a constant temperature drying oven at 250°C for 3 hours. During the drying process, water and most organic components are fully removed to form a brown, uniformly structured gel precursor with a certain porosity. The keratin is partially carbonized, providing a template for subsequent crystal nucleation and creating a microporous structure for the formation of LLZO particles. The process is as follows Figure 1 shown.

[0057] 6. Place the dried gel precursor into a corundum crucible and place it in a muffle furnace. In an air atmosphere, heat it to 950°C at a heating rate of 8°C / min and keep it constant for 2 hours. During this high-temperature calcination process, the metal complexes completely decompose and react with each other, eventually forming highly crystalline, pure cubic phase LLZO nanoparticles. After cooling to room temperature, take out the product and grind it into a mortar to obtain a uniform and fine LLZO nanopowder. The process is as follows: Figure 1 shown.

[0058] 7. Material characterization and performance:

[0059] XRD characterization: The XRD spectrum of the prepared powder is as follows Figure 1 As shown, it is similar to the cubic phase Li7La3Zr2O shown in JCPDS card (45-0109) 12 The standard spectrum is highly consistent, all diffraction peaks can correspond to the characteristic peaks of cubic phase LLZO, and no obvious impurity peaks are observed (impurity content is less than 1%), indicating that high crystallinity, pure phase cubic phase LLZO has been successfully prepared. Figure 2 shown.

[0060] SEM characterization: The SEM images of the prepared LLZO nanopowders are shown in Figure 2. Figure 2 As shown in the figure, it presents a uniform nanoparticle morphology with a particle size distribution range of 30-80nm and an average particle size of 52nm. The particles are interconnected to form a porous structure. This shows that the organic template effect of keratin effectively controls the nanoscale and dispersibility of the powder. The test results are shown in the figure. Figure 3 shown.

[0061] The ionic conductivity test was carried out according to the method of Example 7. The room temperature ionic conductivity of the LLZO nanopowder tablets prepared in this example at 25°C was as high as 4.42×10 -4 S cm -1 This performance is significantly better than that of LLZO prepared by traditional solid phase method (usually 10 -5 S cm -1 Level), the electrochemical test results are as follows Figure 4 shown.

[0062] Example 2: Optimization of Keratin Extraction Conditions - Using KOH and Na2S as Reducing Agents

[0063] Keratin extraction and purification:

[0064] Refer to step 1 of Example 1, but adjust the keratin extraction conditions: Weigh 10 g of shredded wool and place it in a 500 mL three-necked flask. Add 200 mL of 0.9 mol / L KOH aqueous solution (pH approximately 13.8) and 0.05 mol / L Na2S as a reducing agent. Stir the reaction in an 80°C water bath for 3 hours at 400 rpm. After the reaction, filter the mixture while hot through a Buchner funnel and alkali-resistant filter paper to separate solid impurities such as undissolved fibers. The filtrate is then dropwise adjusted to pH 4.5 with 1 mol / L hydrochloric acid, followed by centrifugation, washing, and lyophilization to yield approximately 7.8 g of purified keratin powder. The extraction efficiency is approximately 78%.

[0065] LLZO nanopowder performance: The keratin powder obtained above was used to prepare LLZO nanopowder according to the process of steps 3-6 of Example 1. The test was carried out according to the method of Example 8. The room temperature ionic conductivity at 25°C reached 4.02×10 -4 S cm -1 This example demonstrates that KOH as an alkali source and Na2S as a reducing agent can also be used to efficiently extract keratin and prepare cubic LLZO nanopowders with excellent performance. The electrochemical test results are shown in FIG. Figure 5 shown.

[0066] Example 3: Optimization of Keratin Extraction Conditions - Using Lower Concentrations of NaOH and Mercaptoethanol as Reducing Agents

[0067] Keratin extraction and purification: Refer to step 1 of Example 1, but adjust the keratin extraction conditions: 10 g of shredded wool was weighed and placed in a 500 mL three-necked flask. 200 mL of 0.7 mol / L aqueous NaOH (pH approximately 13.2) and 0.06 mol / L mercaptoethanol as a reducing agent were added. The mixture was stirred in an 80°C water bath for 3 hours at 400 rpm. After the reaction, the mixture was filtered while hot through a Buchner funnel and alkali-resistant filter paper to separate solid impurities such as undissolved fibers. The filtrate was then dropwise adjusted to pH 4.5 with 1 mol / L hydrochloric acid, followed by centrifugation, washing, and lyophilization to yield approximately 7.5 g of purified keratin powder, with an extraction efficiency of approximately 75%.

[0068] Preparation and properties of LLZO nanopowder: The keratin powder obtained above was used to prepare LLZO nanopowder according to the process of steps 3-6 of Example 1. The test was carried out according to the method of Example 8. The room temperature ionic conductivity at 25°C reached 4.3×10 -4 S cm -1 The electrochemical test results are as follows. Figure 5 shown.

[0069] Example 4: Fine Optimization of Keratin Extraction Conditions (Using Lower Concentration of Na2S2O3 as Reducing Agent)

[0070] This example aims to verify the effect of slightly reducing the concentration of the reducing agent in Example 1 on the keratin extraction effect and the final LLZO powder performance when the type of reducing agent remains unchanged.

[0071] Keratin extraction and purification: Refer to step 1 of Example 1, but adjust the conditions for keratin extraction: weigh 10g of shredded wool, place it in a 500mL three-necked flask, add 200mL of 0.8mol / LNaOH aqueous solution, and add 0.04mol / LNa2S2O3 as a reducing agent. Stir the reaction in an 80°C water bath for 3 hours, and maintain the stirring speed at 400rpm. After the reaction is completed, filter while hot through a Buchner funnel and alkali-resistant filter paper to separate solid impurities such as undissolved fibers. The resulting filtrate is adjusted dropwise to pH 4.5 with 1mol / L hydrochloric acid, followed by centrifugation, washing, and freeze-drying to obtain approximately 7.7g of purified keratin powder with an extraction efficiency of approximately 77%.

[0072] Preparation and performance of LLZO nanopowder: According to the method of Example 8, the room temperature ionic conductivity at 25°C reached 4.15×10 -4 S cm -1 The electrochemical test results are as follows. Figure 5 shown.

[0073] Example 5: Precursor Metal Source Optimization - Replacing Part of the Metal Precursor with Nitrate

[0074] Refer to step 3 of Example 1, but replace part of the metal salt precursor: replace LiOH·H2O with analytically pure LiNO3 (≥99.5%), and adjust the weighing mass accordingly to ensure an accurate Li:La:Zr:Al:Nb molar ratio.

[0075] Even when using nitrate precursors from different sources, homogeneous and transparent solutions can be obtained.

[0076] The precursor solution prepared by the above optimization scheme was subjected to sol formation, gel drying and calcination according to steps 4-6 of Example 1.

[0077] The ionic conductivity of the obtained solid electrolyte is 4.3×10 -4 S cm -1 The electrochemical test results are as follows. Figure 5 shown.

[0078] Example 6: Optimization of gel drying and calcination conditions

[0079] This example aims to investigate the effects of calcination heating rate and holding time on the microstructure and crystallinity of LLZO nanopowders.

[0080] In this example, based on Example 1, the gel calcination conditions were optimized to verify their effects on the properties of LLZO nanopowder.

[0081] Calcination conditions: In addition to the method of increasing the temperature to 950°C at 8°C / min and holding it for 2 hours in air atmosphere in Example 1, the temperature was increased to 950°C at a heating rate of 6°C / min and held at this temperature for 2.5 hours in air atmosphere;

[0082] The ionic conductivity (25°C) of the LLZO nanopowder prepared under the above optimized conditions can reach 3.80×10 -4 S cm -1 The electrochemical test results are as follows. Figure 5 shown.

[0083] Example 7: Ionic conductivity testing and evaluation of LLZO nanopowders

[0084] 1. Tablet Preparation: 0.5 g of the LLZO nanopowder obtained in Example 1 above was placed in a tableting mold (13 mm diameter). Cold-pressed into dense, round tablets using a hydraulic press at a pressure of 100 MPa. The tablet thickness was controlled between 0.8 mm and 1.2 mm. The resulting tablets were heated in air at a rate of 5°C / min from 20°C to 700°C and held at this temperature for 2 hours to enhance density and mechanical strength and eliminate residual stress.

[0085] 2. Electrode Preparation: A layer of highly conductive platinum (Pt) slurry was uniformly coated on the upper and lower surfaces of the LLZO ceramic press to serve as the ion-blocking electrode. The electrode-coated sample was sintered at 600°C for 30 minutes to ensure good contact between the electrode and the electrolyte sheet.

[0086] 3. Ionic Conductivity Test: The ionic conductivity of the LLZO pellets was measured using electrochemical impedance spectroscopy (EIS). The test was performed on a Zahner Zennium electrochemical workstation. The test frequency range was set to 0.1 Hz to 1 MHz, with an AC voltage amplitude of 10 mV. The test temperature range was 25°C to 100°C, precisely controlled by a temperature-controlled chamber.

[0087] 4. Data processing and results: The measured AC impedance spectrum (Nyquist plot) of LLZO tablets at 25°C is shown in the figure below: Figure 3 As shown. By fitting the AC impedance spectroscopy data with an equivalent circuit (using Zview software), the bulk resistance (Rb) and grain boundary resistance (Rgb) of the LLZO ceramic sheet can be obtained. The total ionic conductivity (σ) is calculated according to the following formula: sigma = L / (R*S) where sigma is the ionic conductivity (S·cm-1 ), L is the thickness of the LLZO sheet (cm), R is the total resistance (Ω), S is the electrode area (cm 2 ).

[0088] At 25°C, the room temperature ionic conductivity of the prepared LLZO nanopowder tablets can reach 4.42×10 -4 S cm -1 The above results show that the LLZO nanopowder prepared by the method of the present invention has excellent lithium ion conductivity and can meet the requirements of solid electrolyte applications. The electrochemical test results are as follows: Figure 5 shown.

[0089] Example 8: Performance test of all-solid-state battery based on LLZO nanopowder

[0090] The application performance of the cubic phase LLZO nanopowder prepared in Example 1 as a solid electrolyte material in all-solid-state batteries was verified.

[0091] 1. Preparation of the Solid-State Electrolyte Membrane: Referring to the "Preparation by Tableting" procedure in Example 6, the LLZO nanopowder obtained in Example 1 was cold-pressed and sintered into a dense ceramic electrolyte sheet. Specifically, the LLZO powder was placed in a 13 mm diameter mold and cold-pressed under a pressure of 100 MPa. The mold was then heated to 700°C in air at a heating rate of 5°C / min and held at this temperature for 2 hours to produce an approximately 1.0 mm thick LLZO ceramic electrolyte sheet.

[0092] 2. Preparation of positive electrode slurry: Weigh nickel-cobalt-manganese ternary material (NCM811) as the active material, SuperP as the conductive agent, and PVDF as the binder, and mix them in a mass ratio of NCM811:SuperP:PVDF = 8:1:1. Disperse these materials in an appropriate amount of N-methylpyrrolidone (NMP) and magnetically stir for at least 12 hours to prepare a uniform positive electrode slurry.

[0093] 3. All-solid-state battery assembly: The prepared cathode slurry was evenly coated onto an aluminum foil current collector and dried in a vacuum oven at 60°C for 12 hours to produce a cathode sheet. A lithium metal sheet (acting as the anode) and an LLZO ceramic electrolyte sheet were placed on top of the cathode sheet and pressed together to form a CR2032 button cell. The battery assembly process was performed in an argon-filled glove box to prevent contact between the materials and water and carbon dioxide in the air.

[0094] 4. Charge-Discharge Cycle Performance Testing: The assembled all-solid-state battery was subjected to charge-discharge cycle testing using a battery testing system (Model: Blue Electric Electrochemical Test System CT-3004A). The voltage range was between 2.8 and 4.3 V, and the charge and discharge current density was 0.2C (1C = 200 mAh / g). The cycle was repeated 100 times, and the discharge capacity, coulombic efficiency, and other data were recorded for each cycle.

[0095] 5. Results: Figure 4 As shown, the all-solid-state battery using the LLZO nanopowder prepared by the method of the present invention as a solid electrolyte has an initial discharge capacity of 188.4 mAh / g after 100 cycles at a current density of 0.2C, and the capacity retention rate after 100 cycles reaches more than 90%, and the coulombic efficiency is stable at nearly 100%. These results fully demonstrate that the LLZO nanopowder prepared by the present invention has excellent cycle stability and electrochemical performance as a solid electrolyte material in all-solid-state batteries, can effectively improve the overall performance of the solid electrolyte membrane, and provide an important foundation for the development of high-performance solid-state lithium-ion batteries. The electrochemical test results are shown in FIG. Figure 6 shown.

[0096] Example 9: Application of LLZO nanopowder in lithium metal anode interface protection

[0097] Preparation of LLZO nano-coated lithium anode:

[0098] The LLZO nanopowder prepared in Example 1 was mixed with a small amount of polyvinylidene fluoride (PVDF) binder at a mass ratio of LLZO:PVDF = 9.5:0.5. The mixture was dispersed in an appropriate amount of N-methylpyrrolidone (NMP) and stirred to form a uniform slurry. This slurry was evenly coated on the surface of a commercial lithium metal sheet (14 mm diameter, 0.2 mm thickness) by doctor blade coating, forming a thin, uniform LLZO nanopowder coating (approximately 5-10 μm thick). The sheet was then dried in a vacuum oven at 60°C for 12 hours to obtain an LLZO-modified lithium anode.

[0099] Symmetrical battery assembly and ultra-long cycle performance testing:

[0100] Two LLZO-modified lithium anodes were assembled into a Li|LLZO-Li symmetric button cell (CR2032 type), with a separator (Celgard2325) and a conventional liquid electrolyte (1MLiPF6inEC:DEC=1:1v / v+1%FEC) in the middle. -2 The lithium stripping / deposition cycle test was carried out at a current density of , and the total cycle time was extended to 700 hours. The electrochemical test results are shown in FIG. Figure 7 shown.

[0101] The results showed that the LLZO-modified symmetrical battery could be cycled stably for over 700 hours with minimal overpotential fluctuation (approximately 30-40 mV) and remained stable after long-term cycling. This indicates that the LLZO nanocoating effectively reduces the side reactions between lithium metal and the electrolyte, forming a stable solid electrolyte interface (SEI) layer, which effectively inhibits the nucleation and growth of lithium dendrites.

[0102] Comparative experiment: Symmetrical batteries with bare lithium negative electrodes that have not been modified with LLZO generally show a significant increase in overpotential within 100-150 hours at the same current density, and fail due to short circuit within 200 hours. This is mainly due to severe lithium dendrite growth and unstable SEI layer. This embodiment fully demonstrates that the LLZO nanopowder prepared by the present invention can significantly improve the interfacial stability of the lithium metal negative electrode, effectively inhibit the formation and growth of lithium dendrites, thereby greatly extending the cycle life and safety of the battery, and providing a key solution for the application of high energy density lithium metal batteries. The electrochemical test results are as follows: Figure 8 shown.

[0103] Example 10: Enhanced Application of LLZO Nanopowder in Solid Polymer Electrolyte (SPE)

[0104] Preparation of LLZO / PEO composite solid electrolyte membrane:

[0105] The LLZO nanopowder prepared in Example 1 (as an inorganic filler) was mixed with polyethylene oxide (PEO, molecular weight 600,000) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) at a mass ratio of PEO:LiTFSI:LLZO = 8:1:1.5. First, PEO and LiTFSI were dissolved in anhydrous acetonitrile and stirred for 12 hours to form a homogeneous solution. Subsequently, the LLZO nanopowder was added to the PEO / LiTFSI solution and ultrasonically dispersed for 1 hour (200 W), followed by magnetic stirring for 24 hours to ensure uniform dispersion of the LLZO nanoparticles in the polymer matrix. The resulting slurry was cast onto a clean polytetrafluoroethylene (PTFE) plate and dried in a vacuum oven at 60°C for 48 hours to produce an approximately 50 μm thick LLZO / PEO composite solid electrolyte membrane.

[0106] Ionic conductivity test:

[0107] The ionic conductivity of the composite solid electrolyte membrane was measured using electrochemical impedance spectroscopy (EIS). The test frequency range was 0.1 Hz to 1 MHz, the AC voltage amplitude was 10 mV, and the test temperature was set at 25°C.

[0108] The results show that the ionic conductivity of the LLZO / PEO composite solid electrolyte membrane prepared in this example reaches 2.19×10 -4S cm -1 The electrochemical test results are as follows. Figure 5 The electrochemical test results are shown in Figure 5 shown.

[0109] Comparative experiment: The ionic conductivity of pure PEO / LiTFSI electrolyte membrane without LLZO at 25°C is 3.05×10 -5 S cm -1 The LLZO nanopowder prepared by the present invention is used as a filler to significantly improve the ionic conductivity of the composite solid electrolyte membrane, and can effectively reduce the crystallinity of the polymer, improve the ion migration path, and improve its thermal stability. The electrochemical test results are as follows Figure 5 shown.

[0110] Mechanical performance evaluation:

[0111] The composite film was subjected to a tensile strength test (universal testing machine, tensile rate 5 mm / min).

[0112] The results show that the tensile strength of the composite film with the addition of LLZO nanopowder is about 25% higher than that of the pure PEO film, reaching 5.5MPa, and the elongation at break remains above 300%. This shows that LLZO particles effectively enhance the mechanical strength and stability of the film, help to suppress internal short circuits in the battery, and improve battery safety. Figure 9 As shown in FIG. , the LLZO nanopowder prepared by the present invention can be used as an inorganic filler to further enhance the synergistic application of solid polymer electrolyte (SPE) in terms of ionic conductivity and mechanical strength.

[0113] Example 11: Applicability of waste wool keratin from different sources

[0114] Pretreatment and keratin extraction of waste wool from different sources:

[0115] In addition to the ordinary waste wool (textile factory scraps) used in Example 1, this example attempts to use waste wool from the following different sources for keratin extraction:

[0116] 10 g of waste cashmere products (such as cashmere sweater scraps) were taken and keratin was extracted according to steps 1-2 of Example 1.

[0117] Purified keratin powder can be successfully extracted from waste wool from other sources, with extraction efficiency similar to that of Example 1 (about 70-85%) and high purity (protein content>90%).

[0118] LLZO nanopowder preparation and properties:

[0119] Ionic conductivity test (25°C): The ionic conductivity of the prepared LLZO tablets is 4.13×10 -4 S cm -1 This proves that the method of the present invention is widely applicable to the sources of waste wool, further broadens the source of raw materials, and improves the universality of resource recycling. Figure 5 shown.

[0120] Comparative Example 1: Preparation of LLZO nanopowder by traditional high temperature solid phase reaction method

[0121] This comparative example describes in detail the process for preparing LLZO nanopowder using a traditional high-temperature solid-phase reaction method and the properties of the obtained product, for comparison with the method of the present invention.

[0122] Preparation Method: Analytically pure oxide or carbonate precursors such as Li2CO3, La2O3, ZrO2, Al2O3, and Nb2O5 were selected. After being accurately weighed according to the target stoichiometric ratio, all powders were placed in a planetary ball mill and subjected to high-temperature milling (400 rpm for 12 hours) to ensure initial uniform mixing. The mixed powders were pressed into tablets and then calcined in a muffle furnace at 1000°C for 12 hours. The calcined product was removed, ground again, and repeated for tableting and a second calcination (1200°C for 10 hours).

[0123] The properties of the obtained product:

[0124] Particle size and morphology: The particle size of LLZO powder prepared by traditional solid phase method is generally in the micron level (2-5μm), with wide particle size distribution and serious agglomeration. It requires multiple grinding to obtain relatively fine powder, but it is still difficult to reach the nanometer level. The SEM test results are as follows Figure 10 shown.

[0125] Purity and crystallinity: Since the solid phase reaction is carried out by diffusion between particles, the reaction is not complete, and the content of impurities (such as La2Zr2O7, Li2CO3, etc.) is usually higher than 5%, and the impurity peaks are obvious in the XRD spectrum. The crystallinity of the material is relatively low, and there are many grain boundary defects. The XRD test results are as follows Figure 11 shown.

[0126] Ionic conductivity: Limited by the large particle size, severe agglomeration, high impurity content and rough grain boundaries, its ionic conductivity is low, about 3.4×10 -5 S cm -1 The grain boundary impedance is large, which seriously affects the transmission efficiency of lithium ions in the material. Figure 5 shown.

[0127] Energy consumption and operation: This method requires high temperature and multiple long-term calcination, resulting in high energy consumption; and the process is complex, requiring repeated grinding and tableting, which is cumbersome to operate and easily introduces impurities during the grinding process.

[0128] Comparative Example 2: Preparation of LLZO nanopowder by conventional multi-step sol-gel method (without adding keratin)

[0129] This comparative example describes in detail the process for preparing LLZO nanopowder using a conventional multi-step sol-gel method (without the aid of keratin) and the properties of the obtained product for comparison with the method of the present invention.

[0130] Preparation method: Metal salts such as LiNO₃, La(NO₃)₃·6H₂O, Zr(NO₃)₄·5H₂O, Al(NO₃)₃·9H₂O, and NbCl₅ are selected as precursors. Each metal salt is dissolved individually or as a mixture in deionized water or an organic solvent. Citric acid is added to aid in sol formation, and the hydrolysis and polycondensation reaction conditions are strictly controlled. After the sol is formed, it is slowly dried (at 80°C under vacuum for 3 days) to form a gel. Subsequently, the gel undergoes an initial low-temperature pretreatment (e.g., 500°C) to remove most organic matter, followed by high-temperature calcination (1000°C for 10 hours) to obtain LLZO.

[0131] The properties of the obtained product:

[0132] Particle size and morphology: Conventional multi-step sol-gel method can produce nano-scale LLZO powder, the particle size is usually between 100-300nm. However, due to the lack of efficient natural complexing and template agents such as keratin, the particles still have a certain degree of agglomeration during the formation process, and the dispersion is not as good as the method of the present invention. The SEM test results are as follows Figure 12 shown.

[0133] Purity and crystallinity: Although the sol-gel method can obtain relatively pure products compared to the solid phase method, due to incomplete decomposition of the organic complexing agent or improper control of calcination conditions, impure Li2CO3 is often present after calcination. Figure 13 shown.

[0134] Ionic conductivity: The ionic conductivity has been improved to about 3.69×10 -5 S cm -1 However, due to the agglomeration of nanoparticles and the impurities at the grain boundaries, additional ion transport barriers are still formed. Figure 5 shown.

[0135] In summary, this invention utilizes keratin as a natural macromolecular complexing agent and organic template, effectively promoting the uniform dispersion of metal ions in the precursor, simplifying the preparation process, and successfully producing cubic LLZO nanopowders with a particle size of 30-100 nm, high purity, and high crystallinity through a Nb / Al co-doping strategy. This method is environmentally friendly and achieves high-value utilization of waste resources. The resulting powders exhibit excellent ionic conductivity and electrochemical properties, and have broad application prospects in the field of solid-state batteries.

Claims

1. A method for preparing LLZO nanopowder by a keratin-assisted sol-gel method, characterized in that The method comprises the following steps: S1: preparing a precursor solution: adding keratin, lithium source, lanthanum source, zirconium source, aluminum source and niobium source into water and fully dissolving them, and adjusting the pH to 7-9 to obtain a uniform precursor solution; S2 forming a sol: stirring the precursor solution at 80-90° C. for 30-60 min to form a stable sol; S3 forming a gel: drying the sol at 220-250° C. to obtain a gel precursor; S4 calcination: heating the gel precursor to 930° C.-950° C. at a heating rate of 5-10° C. / min, keeping the temperature for 2-3 hours, cooling naturally, and then crushing to obtain the LLZO nanopowder.

2. The method according to claim 1, wherein: The keratin described in S1 is a keratin powder obtained by treating waste wool in an alkaline reducing solution, followed by chain scission, precipitation, centrifugation, washing and drying.

3. The method according to claim 2, wherein: The keratin is extracted using a 0.5-1 mol / L NaOH or KOH aqueous solution supplemented with 0.1 mol / L Na2S, 0.05 mol / L Na2S2O3 or 0.05 mol / L mercaptoethanol as a reducing agent.

4. The method according to claim 1, wherein: In the precursor solution S1, the molar ratio of each metal element is: Li is 6.5-7.5; La is 2.8-3.2; Zr is 1.8-2.2; Al is 0.1-0.5; Nb is 0.05-0.3; based on 100 mL of water, the amount of keratin used is 20g-60g.

5. The method according to claim 1, wherein: In S1, the lithium source is lithium hydroxide, the lanthanum source is lanthanum nitrate, the zirconium source is zirconyl nitrate, the aluminum source is aluminum nitrate, and the niobium source is niobium pentachloride.

6. An LLZO nanopowder prepared by the method according to any one of claims 1 to 5.

7. The LLZO nanopowder according to claim 6, characterized in that: The obtained LLZO nanopowder has a particle size range of 30-100 nm, a stable cubic phase crystal structure, and an impurity content of less than 2%.

8. Use of the LLZO nanopowder according to claim 6 in preparing a solid electrolyte membrane.

9. Use of the LLZO nanopowder according to claim 6 in stabilizing the interface of a lithium metal negative electrode.

10. Use of the LLZO nanopowder according to claim 6 in the preparation of positive electrode materials.